The role of green marketing: insights from three airline case studies - Mayer, Robert; Ryley, Tim; Gillingwater, David (Greenleaf, 2014)
The purpose of this paper is to show how airlines incorporate green elements in their marketing mix and how these changes are communicated to the public. Based on an examination of airlines' websites and publications as well as a review of academic and industry literature, three airline case studies on Virgin Atlantic Airways, easyJet and Flybe are developed. A multiple case design is applied that provides an in-depth review of the airlines' environmental activities and enables differences between their green marketing activities to be identified. All three airlines have adapted their marketing mix to address the environmental impacts of air transport. While there are some commonalities between the airlines (e.g. market communications addressing green credentials), there are also some differences in how the airlines approach the issue. Services are often seen as low-impact industries when it comes to environmental impacts, yet there are certain service sectors that have recognisable environmental impacts. The airline sector has received considerable attention regarding their emissions and they have responded to negative coverage of their environmental impacts. The paper presents an original multiple case study of the green marketing of three airlines. It provides a comparison between three airlines and highlights commonalities as well as differences in green marketing of the three airlines.